Dumb and dumber to [videorecording (DVD)] - Farrelly, Bobby, 1958-; Farrelly, Peter; Carrey, Jim, 1962-; Daniels, Jeff, 1955-; Turner, Kathleen, 1954- ([Publisher not identified], 2015)
Lloyd and Harry go on a road trip to find a child Harry never knew he had, and the responsibility neither should ever, ever be given.